The status of soil organic carbon under indigenous forests, grasslands, wetlands and pine plantations in Woodbush, Limpopo Province, South Africa - Mongwe, Hlamalani Godfrey (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric)--University of Stellenbosch, 2004.